Susceptibility to hypertension based on MTHFR rs1801133 single nucleotide polymorphism and MTHFR promoter methylation - Chiu, Ming-Huang; Chang, Chia-Hsiu; Tantoh, Disline Manli; Hsu, Tsui-Wen; Hsiao, Chih-Hsuan; Zhong, Ji-Han; Liaw, Yung-Po (Frontiers in Cardiovascular Medicine, 2023)
Background The aetio-pathologenesis of hypertension is multifactorial, encompassing genetic, epigenetic, and environmental factors. The combined effect of genetic and epigenetic changes on hypertension is not known. We evaluated the independent and interactive association of MTHFR rs1801133 single nucleotide polymorphism (SNP) and MTHFR promoter methylation with hypertension among Taiwanese adults. Methods We retrieved data including, MTHFR promoter methylation, MTHFR rs1801133 genotypes (CC, CT, and TT), basic demography, personal lifestyle habits, and disease history of 1,238 individuals from the Taiwan Biobank (TWB). Results The distributions of hypertension and MTHFR promoter methylation quartiles (β < 0.1338, 0.1338 ≤ β < 0.1385, 0.1385 ≤ β < 0.1423, and β ≥ 0.1423 corresponding to <Q1, Q1–Q2, Q2–Q3, and ≥Q3) among individuals with the rs1801133 genotypes (CC, CT, and TT) were significantly different (P < 0.05). The risk of hypertension was significantly higher among individuals with the TT genotype compared to the reference genotype (CC): odds ratio (OR); 95% confidence interval (CI) = 2.718; 1.503–4.914. The trend of the association of the CT and TT genotypes with hypertension was dose-dependent (P-trend = 0.0041). MTHFR promoter methylation (lower quartiles compared to ≥Q3) was not significantly associated with hypertension. However, its interaction with MTHFR rs1801133 was significant (P = 0.0323). After stratification by rs1801133 genotypes, lower MTHFR promoter methylation quartiles (<Q1, Q1–Q2, Q2–Q3) compared to ≥Q3 were significantly associated with a higher risk of hypertension among individuals carrying the CC genotype: ORs (95% CIs) = 3.225 (1.140–9.124), 4.177 (1.424–12.247), and 8.645 (2.513–29.739) for Q2–Q3, Q1–Q2, and <Q1, respectively. The trend test was significant (P-trend = 0.0009). Conclusion Independently, rs1801133 TT was associated with a higher risk of hypertension, but methylation was not. Based on genotypes, lower methylation was dose-dependently associated with a higher risk of hypertension in individuals with the CC genotype. Our findings suggest that MTHFR rs1801133 and MTHFR promoter methylation could jointly influence hypertension susceptibility.